Ultrafast dissociation of ammonia: Auger Doppler effect and redistribution of the internal energy. Issue 10 (23rd February 2022) - Travnikova, Oksana; Kukk, Edwin; Hosseini, Farzad; Granroth, Sari; Itälä, Eero; Marchenko, Tatiana; Guillemin, Renaud; Ismail, Iyas; Moussaoui, Roba; Journel, Loïc; Bozek, John; Püttner, Ralph; et al.
Abstract : Vibrationally-resolved resonant Auger electron–photoion coincidence measurements allow observing the Auger–Doppler effect in ammonia following ultrafast dissociation. About 43% of the internal energy left in the system is transferred to vibrations. Abstract : We study vibrationally-resolved resonant Auger (RAS) spectra of ammonia recorded in coincidence with the NH2 + fragment, which is produced in the course of dissociation either in the core-excited 1s −1 4a11 intermediate state or the first spectator 3a −2 4a11 final state. Correlation of the NH2 + ion flight times with electron kinetic energies allows directly observing the Auger-Doppler dispersion for each vibrational state of the fragment. The median distribution of the kinetic energy release E KER, derived from the coincidence data, shows three distinct branches as a function of Auger electron kinetic energy E e : E e + 1.75 E KER = const for the molecular band; E KER = const for the fragment band; and E e + E KER = const for the region preceding the fragment band. The deviation of the molecular band dispersion from E e + E KER = const is attributed to the redistribution of the available energy to the dissociation energy and excitation of the internal degrees of freedom in the molecular fragment. We found that for each vibrational line the dispersive behavior of E KER vs. E e is very sensitive to the instrumental uncertainty in the determination of E KER causing the competition between the Raman ( E KER + E e = const) and Auger ( E e = const) dispersions: increase in the broadening of the finite kinetic energy release resolution leads to a change of the dispersion from the Raman to the Auger one.